Psycho-Cultural Process of Language Acquisition and Development: A Critical Review: Psycho-Cultural Process of Language Acquisition - Abdulhay, Husain (LANGUAGE ART, 2025)
This study endeavors to canvass critically the cultural processes involved in language acquisition from the psychological point of view. To discern how the culture enacts and interacts with mind in shaping and sculpting of the language is the focus of the present review. An overview of the studies on the mutual interplay between culture and thought process and their reciprocal interactions will be, in detail, presented to signpost the path to the determining players. The evidences from all walks of cultures across different contexts yielded to corroborate the claims provided for the actual differences and semblances. A broader footwork, discussing of the empirical and theoretical evidences with the provision of implications and applications of the study will also ensue.